Pendampingan Aparatur Desa dalam Pemanfaatan Sistem Informasi Desa Untuk Pengelolaan Data Kependudukan - Dwi Rahayu Susanti; M.Taufik Hidayat; Lodia Sari; Raodatul Amni; Haerurrasikin (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Accurate, up-to-date, and integrated population data management is essential for effective village governance and public service delivery. However, many village officials still face challenges in utilizing information technology to manage population data efficiently. This community service activity aimed to enhance the capacity of village officials in utilizing the Village Information System (VIS) as a tool for more organized, accurate, and efficient population data management. The methods employed included socialization sessions, training, hands-on practice, and technical assistance in operating the system. The implementation process consisted of needs assessment, training delivery, practical exercises in data entry and updating, and evaluation of the assistance outcomes. The results showed a significant improvement in the knowledge and skills of village officials in managing population data through the Village Information System. Furthermore, the quality of population data became more structured, easily accessible, and supportive of administrative service delivery to the community. The assistance program also contributed to improving the effectiveness of village officials’ performance in providing accurate demographic information for planning and decision-making purposes. Therefore, the utilization of the Village Information System through continuous assistance has proven effective in supporting data-driven and accountable village governance